Complications of choledochoduodenostomy - Colet, Andrés; Sojo, Enrique; Beguiristain, Alberto; Estefan, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1993)
Choledochoduedonostomy is an excellent biliodigestive derivation; very good results are obtained if it is correctly indicated and soundly performed from the technical point of view.